Influence of vacancy diffusional anisotropy: Understanding the growth of zirconium alloys under irradiation and their microstructure evolution. (15th August 2020) - Christiaen, B.; Domain, C.; Thuinet, L.; Ambard, A.; Legris, A.
Abstract: In this work, we propose a series of Object Kinetic Monte Carlo simulations complemented by an analytical model that allows rationalizing a certain number of experimental facts related to the growth of high purity, recrystallized zirconium alloys under irradiation. Our vision of the phenomenon rests essentially on vacancy diffusion anisotropy (with faster diffusion in the basal planes than perpendicular to them) that is necessary to lead to the formation of layers of prismatic interstitial dislocation loops parallel to the basal plane. The acceleration of the deformation under irradiation and this localization of the damage are strongly connected. An analytical model developed using the concepts of difference of anisotropic diffusion between vacancies and interstitials makes it possible to account for the observed phenomena. Graphical abstract: Image, graphical abstract